Transparent luminescent solar concentrators using Ln3+-based ionosilicas towards photovoltaic windows - Frias, Ana R. (2021)
The integration of photovoltaic (PV) elements in urban environments is gaining visibility due to the current interest in developing energetically self-sustainable buildings. Luminescent solar concentrators (LSCs) may be seen as a solution to convert urban elements, such as façades and windows, into energy-generation units for zero-energy buildings. Moreover, LSCs are able to reduce the mismatch between the AM1.5G spectrum and the PV cells absorption. In this work, we report optically active coatings for LSCs based on lanthanide ions (Ln3+ = Eu3+, Tb3+)-doped surface functionalized ionosilicas (ISs) embedded in poly(methyl methacrylate) (PMMA). These new visible-emitting films exhibit large Stokes-shift, enabling the production of transparent coatings with negligible self-absorption and large molar extinction coefficient and brightness values (~2 × 105 and ~104 M−1∙cm−1, respectively) analogous to that of orange/red-emitting organic dyes. LSCs showed great potential for efficient and environmentally resistant devices, with optical conversion efficiency values of ~0.27% and ~0.34%, respectively.